Frequency of Various Factors that Lead to Conversion of Laparoscopic Cholecystectomy to Open Cholecystectomy - Shakil, Fahad; Jalil, Meezan; Umer, Waleed; Faiz, Muhammad Salman (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of various factors that lead to the conversion of laparoscopic cholecystectomy to open cholecystectomy.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of General Surgery, Combined Military Hospital Rawalpindi, Pakistan, from Aug 2020 to Aug 2022.Methodology: One hundred and twenty-four individuals who had symptomatic gallstones and were scheduled to have laparoscopic cholecystectomy were included. For patients in whom laparoscopic surgery was converted to an open procedure, the factors leading to this conversion were assessed.Results: In our study, median age was 51.00 (70.00–21.00) years, 47(37.90%) males and 77(62.10%) females. Patients with ASA status I comprised 94(75.81%), while those with ASA status II comprised 30(24.19%). The median BMI was 21.50 (17.00–44.00) kg/m². The conversion frequency of laparoscopic cholecystectomy into open cholecystectomy was 13(10.48%). The most common factors that led to this conversion were older age 4(30.77%) and obesity 4(30.77%), followed by male gender 2(15.38%), history of previous abdominal surgery 2(15.38%) and poor condition of gall bladder (GB) prior to surgery 1(7.70%).Conclusion: The conversion frequency of laparoscopic cholecystectomy into open cholecystectomy was 10.48%. The most common factors that led to this were older age and obesity.